PENGEMBANGAN POTENSI KELOMPOK WANITA TANI UNIT PEMUKIMAN TRANSMIGRASI PULAU MALAN KABUPATEN KATINGAN PROVINSI KALIMANTAN TENGAH - YUANITA, IIS -; SILITONGA, LISNAWATY; -, PAULINI (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015, 2015)
The purpose of this activity was to develop small industries of animal products at transmigration sites by women’s empowerment. The rural women could improve not only the animal products such as meats, eggs, seeds of duck and chicken, but also local and regional income. In addition to improving the ability of rural women in business by utilizing commodity Alabio and chicken as a superior product. When animal products processing into food products, it could provide high economic value and benefits up to 100%. This Community Service was carried out for 8 months from March to October 2012 in UPT Pulau Malan Katingan. The methods consisted of 1) Socialization and counseling to educate the partner group (women farmers group) about Alabio Ducks and Native Chicken farming, accompanied by the demplot of both animal, 2) Training and demonstration of animal products such as egg shredded (egg abon), cracker scrabbed and organic manure, and3) Evaluation and monitoring. Establishment of women farmers group in two partner area was the first result of this activity. The program activities, socialization,demonstration demplots, training and monitoring have a very good response from the partners as well as being inspiration to promote and develop the potential of the group.Implementation of Alabio ducks and native chickens farming succeed to improve the productivity in terms of quantity(number of livestock and bodyweight) and quality(body health andvitality of animals). The animal products processing such as egg shredded (egg abon), cracker scrabbed and organic manure also create new revenue sources for the group of partners. Keywords: Women Farmers Group, UPT PulauMalan, DucksAlabio, Native Chicken, Processed Products